A comparison of the Plusoptix S09 with an autorefractometer of noncycloplegics and cycloplegics in children. Issue 35 (August 2016) - Won, Jae Yon; Shin, Hye Young; Kim, Su Young; Lee, Young Chun
Abstract : Abstract: The aim of the study is to compare outcome measures of refractive error obtained using the Plusoptix S09 photorefractor and an autorefractometer of noncycloplegics and cycloplegics in children. We reviewed the medical records of 40 patients (77 eyes) who were classified using 2 methods. The patients were first assigned to 2 groups consisting of 11 eyes with ≥+3.0 D and 66 eyes with <+3.0 D, and then to 2 groups of 12 and 65 eyes with cycloplegic and noncycloplegic refraction of spherical powers ≥+2.0 D and <+2.0 D, respectively. We compared the outcome measures of refractive error using the Plusoptix S09 photorefractor and an autorefractometer of noncycloplegics and cycloplegics. There was no statistically significant difference between the Plusoptix S09 photorefractor and cycloplegic autorefractometer in the spherical power and spherical equivalent. In contrast, there was a statistically significant difference between the Plusoptix S09 photorefractor and noncycloplegic autorefractometer ( P  < 0.001). There was a statistically significant difference between the spherical equivalent of the Plusoptix S09 photorefractor and cycloplegic autorefractometer in children with hyperopia ≥+3.0D and with cycloplegic and noncycloplegic refraction of spherical power ≥+2.0 D. We also found a significant difference between the outcomes of the Plusoptix S09 photorefractor and cycloplegic autorefractometer in the spherical power and spherical equivalent for children with hyperopia ≥+3.0 D. The refractive error of the Plusoptix S09 photorefractor was similar to that of the cycloplegic autorefractometer, in contrast to the noncycloplegic autorefractometer. However, the Plusoptix S09 photorefractor is an inaccurate tool to estimate the refractive errors of children with moderate hyperopia.